Quantum Optics Innovations for the Future of Quantum Communications - Guijiao Zou; Lie Jie; Cai Jixiong (Yayasan Adra Karima Hubbi, 2024)
Quantum communication is a rapidly evolving field aimed at overcoming security challenges in modern communications. Challenges such as signal degradation and vulnerabilities to classical attacks necessitate new innovations to enhance the efficiency and security of quantum communications. This research explores potential innovations in quantum optics to advance future quantum communications. The primary focus is the development of new techniques that could improve transmission efficiency and enhance the security of quantum communications. The research methodology utilizes a combination of theoretical analysis and laboratory experiments. A review of recent literature in quantum optics is conducted to identify potential innovations that could enhance quantum communications. Subsequently, laboratory experiments are performed to validate the effectiveness of the proposed concepts. The findings indicate various potential innovations in quantum optics that could enhance quantum communications. Techniques such as using entanglement to enhance transmission security and developing more efficient quantum signal processing systems have shown promising results in laboratory trials. This research highlights the importance of innovations in quantum optics as solutions to challenges in quantum communications. By integrating these new concepts into the quantum communication infrastructure, it is expected to improve the efficiency, speed, and security of future quantum communications. Thus, innovations in quantum optics have significant potential to transform the landscape of quantum communications and bring about important advancements in the field.